Волинська «Просвіта» в боротьбі за національне відродження - Понєдєльник, Лариса Анатоліївна (My University, 2016)
У статті зроблено спробу проаналізувати початки зародження волинської «Просвіти», охарактеризувати її діяльність на певних етапах та боротьбу за національне відродження в умовах Польської держави в 1921–1939 рр. Увагу акцентовано на ролі літературного процесу, видавництв і бібліотек.The article attempts to analyse the origins of the origin of Volyn enlightenment to characterize its activity at certain stages and the struggle for national revival in the conditions of the Polish state sn 1921-1939 Focuses on the role of the literary process in particular on the example of the individual poets writers publicists which made a significant contribution to the national culture of the Ukrainian community. Highlights the trends and achievements of libraries - the main means of increasing the General educational and cultural level of the population literacy fight for home scool teaching children the Ukrainian language. Highlight the publishing activities of educational cells as the mirror of political social and cultural life of region.
Volyn Education in the Struggle for National Revival
Keywords: національне відродження; культурне життя; інтелігенція; публіцистика; бібліотека; national revival; a cultural life; intellectuals; journalism; publishing; library